2013
DOI: 10.1159/000355179
|View full text |Cite
|
Sign up to set email alerts
|

Common Blue Nevus withSatellite Lesions Needs aDifferential Diagnosis from Malignant Melanoma

Abstract: Malignant blue nevus is rare, and a common blue nevus rarely needs a differential diagnosis from malignant melanoma. Although a melanocytic nevus with a satellite lesion is usually suggestive of a peripherally disseminating malignant melanoma, very few cases of blue nevus with satellite lesions have been reported thus far. To our knowledge, this is the seventh case of a blue nevus with satellitosis. Periappendageal and perivascular concentrations of the nevus cells were observed in the main papule as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Multiple small similar satellite lesions were visualized. These appeared consistent with previously reported blue nevi termed plaque-type blue nevus (11). Satellite lesions may form by spread along appendegal or perivascular structures, or in a larger field of dermal melanocytosis (12).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Multiple small similar satellite lesions were visualized. These appeared consistent with previously reported blue nevi termed plaque-type blue nevus (11). Satellite lesions may form by spread along appendegal or perivascular structures, or in a larger field of dermal melanocytosis (12).…”
Section: Discussionsupporting
confidence: 92%
“…There have been five cases of blue nevus with satellitosis reported to date (7,(11)(12)(13)(14). Table 1 shows the Table 1 -Demographic characteristics of previously reported cases of blue nevus with satellitosis (7,(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…A special pattern of distribution, a BN in the centre encircled by small satellite lesions, resembling a locally disseminating melanoma, has also been described (Fig. b) . As histopathology of the main naevus lesion and the satellite lesions revealed infiltration of the BN cells along perivascular areas in these cases, the authors suggested that spreading of the dendritic cells via perivascular spaces might be the explanation of this pattern …”
Section: Classical Variants Of Dermal Melanocytosesmentioning
confidence: 85%
“…In conclusion, we suggest that if multiple eruptive pigmented lesions resembling BN are present, a biopsy should always be performed for a differential diagnosis with malignant or metastatic melanoma [ 1,3,[8][9][10][11] .…”
Section: Discussionmentioning
confidence: 89%
“…Eruptive blue nevi (EBN) have rarely been described [ 2,[5][6][7][8][9][10][11] . De Giorgi and colleagues [ 1 ] reported a case of EBN of the penis in an adult patient.…”
Section: Discussionmentioning
confidence: 99%